2020
DOI: 10.1139/cjp-2018-0602
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of heat transfer analysis of fractional Maxwell fluid by using Caputo and Caputo–Fabrizio derivatives

Abstract: A comparative analysis is carried out to study the unsteady flow of a Maxwell fluid in the presence of Newtonian heating near a vertical flat plate. The fractional derivatives presented by Caputo and Caputo–Fabrizio are applied to make a physical model for a Maxwell fluid. Exact solutions of the non-dimensional temperature and velocity fields for Caputo and Caputo–Fabrizio time-fractional derivatives are determined via the Laplace transform technique. Numerical solutions of partial differential equations are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Findings from Raza et al [11] are in good agreement with Raza [10]. Moreover, a comparative study between Caputo and Caputo-Fabrizio using the same condition as that of Raza [10] and Raza et al [11] were published by Raza et al [12]. In the same year, Anwar and Rasheed [13] investigated the effects of fractional derivatives on Oldroyd-B nanofluid flow using the Caputo derivative.…”
Section: Introductionsupporting
confidence: 57%
“…Findings from Raza et al [11] are in good agreement with Raza [10]. Moreover, a comparative study between Caputo and Caputo-Fabrizio using the same condition as that of Raza [10] and Raza et al [11] were published by Raza et al [12]. In the same year, Anwar and Rasheed [13] investigated the effects of fractional derivatives on Oldroyd-B nanofluid flow using the Caputo derivative.…”
Section: Introductionsupporting
confidence: 57%
“…Na et al [10] analyzed free convection Maxwell nanofluid flow between vertical plates with the influence of thermal radiation. Raza and Asad [11] derived the solutions of Maxwell fluid flow considering a vertical flat plate. ey observed that increasing the fluid velocity with respect to Grashof number (Gr) and Maxwell parameter λ. e numerical solutions were obtained by Sui et al [12] calculating the Maxwell nanofluid over stretching sheet with the influence of heat and mass transfer using the homotopy analysis process.…”
Section: Introductionmentioning
confidence: 99%
“…Asjad et al [17] presented the comparisons between Caputo and Caputo-Fabrizio fractional derivatives on second-grade fluid over Newtonian heating. Raza and Ullah [18] used the fractional Maxwell fluid to compare the fractional derivatives of C and CF using the Laplace transformation. Maxwell fluid's natural convection between two parallel plates was discussed by Wang et al [19].…”
Section: Introductionmentioning
confidence: 99%